Injúria Renal Aguda no Pós-operatório de Fratura de Fêmur em Idosos: Associação com Tempo de Internação e Mortalidade - Sá, Saulo Lacerda Borges de (2024)
Major orthopedic surgeries in elderly patients are increasingly common. Proximal femur fractures are more common in the elderly and are associated with chronic functional disability. Early stabilization of fractures is the recommended treatment, as it contributes to reducing morbidity and mortality rates. Postoperative renal dysfunction has been shown to increase mortality. The objective of this project is to evaluate the association between acute kidney injury in the postoperative period of proximal femur fracture with mortality outcomes and length of stay. This is a retrospective data evaluation study using MIMIC-IV. Elderly patients with fractures of the proximal femur who underwent surgery between 2008 and 2019 were included. Based on the evaluation of this database, demographic data, type of fracture, time from fracture to hospital admission, waiting time until surgery, previous diagnosis of osteoporosis, Charlson comorbidity index and association of these data with the diagnosis of acute renal failure. We found that age, male sex, no surgical intervention, the CCI and AKI stage were independently related to one-year survival. Our main findings included first determining the main variables associated with one-year mortality, including severe AKI (stage 2 and 3). We also further explored the association between severe AKI and one-year mortality and revealed that the CCI is an important moderator of this association. Our data revealed that patients with reduced comorbidities (CCI<8) and, consequently, a longer life expectancy are more impacted by long-term outcomes due to severe AKI. In contrast, AKI had no association with a high CCI. Keywords: Hip Fractures. acute kidney injury. Orthopedic Procedures.